Validity study of the EPOCH Measure of Adolescent Well-being in Malaysian samples - Yusoff, Siti Rashidah; Hoesni, Suzana Mohd; Rosharudin, Nur Afrina; Muhammad, Noor Azimah (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2024)
The EPOCH (Engagement, Perseverance, Optimism, Connectedness, Happiness) Measure of Adolescent Well-being is a newly developed scale designed to evaluate adolescent well-being and positive functioning. This study assesses its validity and reliability in a Malay language version. A total of 444 participants (189 boys and 255 girls) aged 13 and 14 were recruited from public schools in Malaysia. The EPOCH measure demonstrated excellent construct, convergent, concurrent, and discriminant validity, as well as reliability, in the sample. Confirmatory factor analysis showed an adequate model fit (CMIN/df = 2.99, RMSEA = .07, CFI = .91, GFI = .90, TLI = .89), while all the subscales had composite reliability above .70, indicating satisfactory convergent validity. The measure and its subscales exhibited significant positive correlations with cognitive reappraisal (CR), ranging from .21 to .31 (p < .01), and negative correlations with expressive suppression (ES), ranging from .04 to .18 (p < .01). Two subscales (engagement and perseverance) showed non-significant correlations with ES, while discriminant validity showed negative correlations with depression, anxiety and stress (r = .14 to .54, p < .01), except for the engagement subscale. It is concluded that the EPOCH measure is valid and reliable for assessing adolescent well-being in Malaysia, providing culturally relevant instruments for such assessment.